Adverse Childhood Experiences and Socio-Emotional Needs of Emerging Adults Through the Lens of Choice Theory - Asante, Akua Bema; Acquaye, Hannah E.; Baah-Binney, Victoria (Advances in Social Sciences Research Journal, 2026)
Adversities at all stages of life can have far-reaching consequences. Some socio-emotional needs of emerging adults stem from attachment with primary caregivers, and when these attachments go awry, therapy can help in repairing these ruptures. This study used Glasser’s Choice theory to explore the adverse childhood experiences of 15 emerging adults (nmale = 6; nfemale = 9) who had been purposively sampled. Using Braun and Clarke’s (2006) thematic analysis framework, three main themes were extracted from the transcribed verbatim interviews. The themes were consistent with three unique developmental stages – childhood, adolescence, and emerging adulthood. While multiple sub-themes emerged from each of the developmental stages, the final stage was grounded on Choice theory in exploring narratives on avoidance, unmet needs, and belongingness. Recommendations are proffered for emerging adults, family therapists, and agencies that work with adolescents and young adults.